Current status of bicompartmental arthroplasty - Yingjian Gao; Bing Yue; Weiwei Xin (Arthroplasty)
Abstract Background Bicompartmental arthroplasty (BCA) serves as a less invasive alternative to total knee arthroplasty. This review aims to present the current status of BCA. Body Recent literature on BCA was reviewed and synthesized from the perspectives of function, radiological assessment, patient satisfaction, survival rate, patellar tracking, satisfaction survey, and revision rate. Conclusion BCA is beneficial for patients with bicompartmental arthritis and those suffering from deterioration in other compartments after unicompartmental knee arthroplasty (UKA). Compared to total knee arthroplasty, BCA reduces trauma, accelerates recovery, and improves sports ability. While BCA is evolving towards a more exciting future, more clinical studies are warranted to exploit its potential and validate its efficacy, eventually improving outcomes and patient satisfaction.